The Relationship Between Concentration and Gate-In Stroke Results in Woodball - Gita Crysdiani; Komarudin Komarudin; Mochamad Yamin Saputra; Geraldi Novian; Rere Anne Marisa Nuraini (Universitas Negeri Semarang, 2026)
The gate-in punch in the sport of woodball is the final blow that determines the final outcome of the game. Therefore, gate-in punches are considered the most crucial punches because they require high accuracy, full concentration, as well as precise punching techniques. This study aimed to determine the relationship between concentration level and the outcome of gate-in strokes of woodball athletes. The method used in this study is a quantitative method involving fifteen active members of UKM Woodball UPI using a correlational research design. The instrument used in the study was in the form of a test that was given once to the sample. The punch test refers to the parking instrument and the gate-in punch Putu (2015). The concentration test is in the form of the Concentration Grid Test from Harris and Bette L. Results: The results of the study showed that there was a significant relationship between concentration and the result of getting strokes in the sport of woodball. This is shown by the results of more accurate punches. This study concludes that concentration plays an important role when making a gate-in punch. So we recommend that woodball coaches should include concentration exercises as an integral part of their training program.